RETRACTED: Innovative trends in professional education in the beauty industry as a factor in the sustainable development of the consumer services industry - Osipova Yulia; Kazmina Lyudmila (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001